Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1001/jamaoto.2016.3964
|View full text |Cite
|
Sign up to set email alerts
|

Technique and Preliminary Analysis of Drug-Induced Sleep Endoscopy With Online Polygraphic Cardiorespiratory Monitoring in Patients With Obstructive Sleep Apnea Syndrome

Abstract: The DISE-PG technique is feasible, safe, and more sensitive at detecting an obstructed breathing pattern than is drug-induced sleep endoscopy alone. The DISE-PG technique could be helpful for accurate comprehension of upper airway obstructive dynamics (ie, degree of obstruction and multilevel pattern) and a nonobstructive breathing pattern (ie, central apneas).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Our patients had an elevated median AHI compared to published norms for children, 27 which supports existing data that preterm infants are more likely to have SDB. 5,6,28 This may be multifactorial, including upper airway obstruction 29 and/or chronic lung parenchymal involvement with low pulmonary reserve. Our patients also had an elevated mean ETCO 2 , which could result from a combination of airway obstruction and ventilation perfusion mismatch secondary to BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Our patients had an elevated median AHI compared to published norms for children, 27 which supports existing data that preterm infants are more likely to have SDB. 5,6,28 This may be multifactorial, including upper airway obstruction 29 and/or chronic lung parenchymal involvement with low pulmonary reserve. Our patients also had an elevated mean ETCO 2 , which could result from a combination of airway obstruction and ventilation perfusion mismatch secondary to BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Early work on this topic was reported in 1996 by Sadoka et al, in a study looking at sleep parameters in natural sleep and comparing it during sleep induced by diazepam and concluded that the findings were similar for non-REM sleep (23). More recent novel studies have addressed this problem by comparing respiratory events during DISE using propofol with natural sleep (4,24). They looked at apnea and hypopnea events and also detected some events in keeping with central apneas.…”
Section: Natural Versus Drug Induced Sleepmentioning
confidence: 99%
“…However, no severe complications have been reported in the DISE literature for children or adults. Complications are predominantly mild and transient, and include desaturation, the need for oxygen supplementation, and sedation instability during the DISE …”
Section: Discussionmentioning
confidence: 99%